A Participação Como Pressuposto da Democracia - Dejalma Cremonese (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2012)
The text discusses the issue of participation as a main premise of democracy. Initially discusses conceptual aspects of participation as "taking part in", share, join the feeling or thought. Shortly after discussing the evolution of Western participation in a democracy, beginning with the pioneering spirit of Classical Greece to the participatory experience of bourgeois liberal democracy in modernity. The third section presents the discussion of participation in contemporary democratic theory, more precisely between the theoretical versus the institutionalists participationist considered. At last, the text points to the importance of the participation in the political and social problem, especially with the experience of the European movement called "Real Democracy Now".